DEMOKRASI PANCASILA DALAM PANDANGAN MOHAMMAD HATTA: SEBUAH KONSEP YANG MULAI MENJAUH DARI AKARNYA - Candra, Atha; Subekti, Anisya Hafsah (Kajian Moral dan Kewarganegaraan, 2025)
This article examines Mohammad Hatta's views on the implementation of Pancasila Democracy in Indonesia and the challenges it faces. Hatta believed that a healthy democracy should involve the active participation of the people and be oriented towards the welfare of the people. Although Pancasila as the foundation of the State contains strong basic values, current democratic practices are often neglected, resulting in public dissatisfaction and reducing the quality of democracy. This research used the literature review method to analyze 100 relevant scientific articles, and after selection, a few articles were obtained that became the focus of analysis. The results show that challenges such as dynastic politics, money politics, low political education, and inaccurate information dissemination contribute to the decline of Pancasila democracy. Therefore, it is important to reflect on the current practice of Pancasila Democracy to keep it in line with Hatta's values and the goals of justice and shared prosperity. Through the inclusive application of Pancasila principles, it is hoped that Indonesian democracy can overcome these challenges and increase public participation in the political decision-making process.